Enhancing Student Learning through Integrated Course Project Activity - Dhulavvagol, Praveen M.; Meti, Anand S.; Kulkarni, Uday N.; Gurlahosur, Sunil V. (Journal of Engineering Education Transformations, 2017)
This paper examines one aspect of the curricular change process undertaken in the undergraduate level in which the inclusive learning community structure changes and support the learning of the students. Many different kinds of student learning are evident in our interview data. A major benefit for students is learning to work in teams, soft skills, directed learning and while all of them spoke of the difficulties involved. The initial changes of the courses are integrated as a course project where the students are interviewed the different aspects of the course in-order to achieve the graduate attributes. In this paper we describe how we carried out the development of integrated course project, So this integrated course project looks at building a network domain applications and realization of basic networking protocols. This integrated course project provides a flavour of combining the Computer Network and Operating System Courses. The conduction of the assessment realizes the students to enquiry the courses in depth and correlate the concepts to a real world problems. It places the responsibility on the individual student to initiate and direct the learning process which provides the contextual environment that makes learning exciting and relevant for the appropriate course. It also provides an opportunity for students to explore technical problems from system level perspective to implementation level. The integrated course also emphasis considerable use of computers in an active learning environment that stressed teaming and other quality tools.